Therapeutic gardens, do they influence the mental health of older adults?: A literature review (LACCEI, 2024)
The population of elderly adults in the world is around 1000 million inhabitants0 one of the main situations they face is the increase in health problems. Another important problem is isolation, due to the loss of contact with family and friends, which can lead to a deterioration of mood, mental well-being and health in general0 one of the strategies that is generating well-being and improving their quality of life is the use of therapeutic gardens. The objective of the research was to determine the importance of therapeutic gardens in the mental health of elderly adults, reported in the scientific literature at the international level between 2018 and 2023. The methodology used was the systematic review of the literature, supported by the PRISMA method. Articles published in Spanish, English and Portuguese were included. The databases were: Scopus, PubMed, Ebsco, ScienceDirect, Dialnet, ProQuest, Scielo and Google Scholar. Articles that were not related to the topic were excluded. The search began with 85053 articles and after applying the inclusion and exclusion criteria it was reduced to 7 articles. It was found that therapeutic gardens improve the physical, mental, psychological, emotional, cognitive, social health and sleep quality of elderly adults0 likewise, they allow a sense of continuity and identity to be maintained by connecting with nature, and promote the improvement of the immune system. Based on the findings, it is suggested that a multidisciplinary work be carried out involving engineers, architects and health personnel for the design and implementation of therapeutic gardens in different areas. The main limitation was the scarce scientific literature on the subject.